Penggunaan Model Group Investigation untuk Meningkatkan Berpikir Kritis Siswa SMP - Vasia Anggis, Eka (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
Group Investigation model is one of cooperatif metode that can grows critical student from directly experience. Based on observation in SMP 1 Indramayu 2016 were 40% the group was less colaboration, 60% evidences was less, 65% students weren’t connected problems each other, 55% decision hadn’t most alternative problem solving to be collected.This aim research to descript critical thingking used group investigation model. Research metode qualititave descriptive, Research parameter is critical skill student and these indicator were problem indentifiy, argument analize, definition, finding source, observasion and result, mind based consideration ability integration to defend decision. Instrument research was quisioner. Result study from quisioner were 78% was good, 71% was enough. Conclusion was critical thinking skill can be used in group investigation model.